Estratigrafia de alta resolução aplicada à modelagem de reservatórios do início do rifte da Bacia de Sergipe - Alagoas - Borba, Cláudio (Universidade do Vale do Rio do Sinos, 2009)
In this work, the results of a tectonic-stratigraphic study on the early rift strata of the Sergipe-Alagoas Basin, northeastern Brazil, were applied to the characterization and modeling of reservoirs. Furado area, a mature oil field, was selected as laboratory because it presents these strata so nearly complete, and has lot of static and dynamic data. We applied a multidisciplinary approach (tectonics, stratigraphy and reservoir characterization) and also a multi-scalar approach (from the context of deposits in the basin to the zoning of producing reservoirs). The 2nd order sequences (K10-20 and K34-K36 corresponding respectively to the Feliz Deserto Formation and Barra de Itiúba/Penedo Formation ) were sliced into 3rd sequences. The stratigraphic analysis suggests that the beginning of rifting process that had already occurred in the Sequence J20-K5 (Serraria Formation) was gradual over 20 Ma. This process is characterized by the absence of a conspicuous unconformity of the onset rift in which the parallel
Keywords: estratigrafia; stratigraphy; Ciências Exatas e da Terra